2004
DOI: 10.1107/s160053680403346x
|View full text |Cite
|
Sign up to set email alerts
|

Methyl 5-hydroxy-2-(2-hydroxy-6-methoxy-4-methylbenzoyl)-3-methoxybenzoate

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean '(C±C) = 0.003 A Ê R factor = 0.063 wR factor = 0.150 Data-to-parameter ratio = 15.1For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Analysis of the HMBC correlations (Table 3, Figure 4) for the left portion of 4 revealed that two chelated hydroxy protons resonating at δ H 12.76 and 13.17 were attributed to 9-OH and 10-OH, respectively. The olefinic proton (δ H 6.20) was assigned as H-6 on the basis of its 3 from the methyl protons (H 3 -12′, δ H 2.24) to C-6′ (δ C 132.9) and C-8′ attached this methyl group at C-7′. A 2-oxopropyl unit was established and located at C-6′ on the basis of the HMBC correlations of H 2 -9′ (δ H 3.93) and H 3 -11′ (δ H 2.30), as demonstrated in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the HMBC correlations (Table 3, Figure 4) for the left portion of 4 revealed that two chelated hydroxy protons resonating at δ H 12.76 and 13.17 were attributed to 9-OH and 10-OH, respectively. The olefinic proton (δ H 6.20) was assigned as H-6 on the basis of its 3 from the methyl protons (H 3 -12′, δ H 2.24) to C-6′ (δ C 132.9) and C-8′ attached this methyl group at C-7′. A 2-oxopropyl unit was established and located at C-6′ on the basis of the HMBC correlations of H 2 -9′ (δ H 3.93) and H 3 -11′ (δ H 2.30), as demonstrated in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…They have produced a broad range of secondary metabolites that show various biological activities. Some of them are the antifungal fungerin, the antibacterial and cytotoxic neomangicols, and the anti- Helicobacter pylori methylsulochrin . We have recently reported the investigation of sea fan-derived fungi that yielded the antibacterial nigrospoxydon A and nigrosporapyrone A .…”
mentioning
confidence: 99%
See 1 more Smart Citation